2020
DOI: 10.1021/acs.jpcb.0c01934
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Protein Folding Triggered by Proton Stripping Generates Inside-Out Structures: A Molecular Dynamics Simulation Study

Abstract: The properties of electrosprayed protein ions continue to be enigmatic, owing to the absence of high-resolution structure determination methods in the gas phase. There is considerable evidence that under properly optimized conditions these ions preserve solution-like conformations and interactions. However, it is unlikely that these solution-like conformers represent the "intrinsic" structural preferences of gaseous proteins. In an effort to uncover what such intrinsically preferred conformers might look like,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 96 publications
9
21
0
Order By: Relevance
“…Radius of gyration vs. time plots revealed that relaxation was complete after ∼30 ns (Figure 3B). In agreement with previous work, 59,88 heatunfolded chains were relatively compact, highly dynamic, showed occasional loose clustering of hydrophobic side chains but did not possess any persistent secondary or tertiary structure. In other words, the relaxation runs of Figure 3 did not cause refolding, which would require much longer time scales (microseconds to seconds) and lower temperatures.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Radius of gyration vs. time plots revealed that relaxation was complete after ∼30 ns (Figure 3B). In agreement with previous work, 59,88 heatunfolded chains were relatively compact, highly dynamic, showed occasional loose clustering of hydrophobic side chains but did not possess any persistent secondary or tertiary structure. In other words, the relaxation runs of Figure 3 did not cause refolding, which would require much longer time scales (microseconds to seconds) and lower temperatures.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The temperature was then ramped from 300 to 1000 K over 100 ns. As demonstrated previously, 88 the highly charged (33+) chains adopted near-linear conformations that did not retain any memory of the native state (Figure 3A, t = 0). Heme was not included, reflecting the labile nature of heme-protein contacts under denaturing conditions, 5 specifically during thermal unfolding.…”
Section: ■ Results and Discussionsupporting
confidence: 70%
“…Equilibrium gas-phase structures of native like proteins give an "inside-out" orientation, with the hydrophobic interior being refolded to the surface of the protein and the external, more hydrophilic portion towards the interior. 67 Therefore, our results, along with of other gas-phase evidence, suggest that kinetically trapped solution-like states are preserved over a typical MS timescale and that inside-out gas-phase equilibrium structures are not populated. The application of a mobility separation prior to ECD allows HDX to be determined as a function of conformational family, a key aspect of this workflow versus workflows that employ fragmentation prior to mobility separation, perform HDX in the mobility cell itself, require post-mobility trapping, or do not have ion mobility.…”
Section: Discussionsupporting
confidence: 62%
“…25,28 Thus, the question of whether gas-phase protein structures correlate with those in solution has been widely investigated. 29 The loss of water molecules may disrupt the balance between hydration and intramolecular protein interactions during transfer of proteins from solution to the gas phase. Soft ionization of ESI has been reported to generate desolvated protein ions whose solution structure features are retained by kinetic trapping.…”
Section: Introductionmentioning
confidence: 99%
“…Ion mobility mass spectrometry (IM-MS) coupled with electrospray ionization (ESI) enables the characterization of ion structures in the gas phase. The experimental collisional cross section (CCS) supported by theoretical three-dimensional modeling is the principal means of characterizing gas-phase ion structures. Electrostatic interactions, which are substantially moderated in high dielectric solvents such as water, dominate protein structures in the gas phase. , Thus, the question of whether gas-phase protein structures correlate with those in solution has been widely investigated . The loss of water molecules may disrupt the balance between hydration and intramolecular protein interactions during transfer of proteins from solution to the gas phase.…”
Section: Introductionmentioning
confidence: 99%